2016
DOI: 10.4236/ojn.2016.63018
|View full text |Cite
|
Sign up to set email alerts
|

Older Patients’ Involvement in Shared Decision-Making—A Systematic Review

Abstract: Shared decision-making has been described as allowing patients to gain more control over their life situation and feel less helpless. The aim of this systematic review was to describe the involvement of older patients in shared decision-making in community settings. In accordance with the systematic review method, a total of 2468 abstracts were read, after which nine quantitative studies were included. A qualitative thematic analysis was performed and two themes emerged; increased understanding of self-managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This can be compared to a study by Foss, in which older adults were found to practice participation in a discrete way and not assume user-involvement as a right (Foss, 2011). It may also be understood as that users are accustomed to traditions that support a passive patient role (Holm, Berland, & Severinsson, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…This can be compared to a study by Foss, in which older adults were found to practice participation in a discrete way and not assume user-involvement as a right (Foss, 2011). It may also be understood as that users are accustomed to traditions that support a passive patient role (Holm, Berland, & Severinsson, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Similar evaluations have been done of in earlier systematic reviews [20] [21]. In this study the PRISMA checklist was employed [22], Table 2.…”
Section: Evaluation Of the Included Studiesmentioning
confidence: 97%
“…Older patients require better support to cope with the emotional consequences of multimorbidity. Healthcare professionals need to change their traditional authoritative role to one that allows them to form partnerships with their patients within a shared decision-making perspective [21]. However, self-management does not always fulfil the aim of autonomy or empowerment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations